The Impact of Service Quality Towards Customer Satisfaction at CV. Four Star Medan: Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada CV. Medan Bintang Empat - Kuandi Chandra; Devia Febrina; Tina Linda (Jurnal Kolaboratif Sains, 2023)
The need to satisfy customer for success in any commercial enterprises is very obvious. A business’s main purpose is to create a customer because it is basically the consumer who essentially determines what a business is. Customers are the sole reason for the existence of commercial establishments. The writer will conduct research at CV. Four Star Medan. It is a cotton manufacturing company for bed Madison which is located at Jalan Veteran Gang Manunggal No. 7 Medan. The writer interviewed the employees of the company regarding the customers, recently the customer complain on the customer service on the delivery, when the delivery is not ontime, the customers asked for the confirmation, the employees do not act quickly to follow up the delivery, the employees sometimes do not give a complete explanation for the warranty time to customers which may lead to to misunderstanding about the products, this is some of their problem related to the service. The problem identifications of the company are how the service quality is implemented in CV. Four Star Medan? And how is the impact of service quality towards customer satisfaction in CV. Four Star Medan. The population of CV. Four Star Medan is the customers more than 3 years of CV. Four Star Medan which are 50 customers. The writer uses Arikunto Sampling theory. The sample size is 50 employees. The writer uses census sampling technique which the writer takes all population as sample. In analyzing data, the writer used some methods such as statistics, normality test, validity test, reliability test, correlation test, determination test, linier regression, and hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result of 0.83 means that service quality has a significantly strong and positive impact towards customer’s satisfaction at CV. Four Star Medan. From the calculation of ztest hypothesis test, the writer got zcount= 5.87. The zcount > ztable (5.87> 1.96), this means the Null hypothesis (Ho) is rejected. The writer can conclude that service quality has impact towards customer satisfaction at CV. Four Star Medan.